2011
DOI: 10.1007/s00247-011-2296-8
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal imaging of amniotic band sequence: utility and role of fetal MRI as an adjunct to prenatal US

Abstract: Fetal MRI is able to visualize amniotic bands and their secondary manifestations and could be complementary to prenatal US when fetal surgery is contemplated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
2
17
0
2
Order By: Relevance
“…This is in agreement with the literature mentioning the difficulty in ultrasound prenatal diagnosis of the amniotic band and the frequent need of simultaneous presence of different congenital deformities to suggest the presence of ABS [16,17]. The use of most recent ultrasound technology (three- and four-dimensional ultrasonography) and the use of magnetic resonance imaging in some cases may improve the diagnosis [9,11,12]. …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is in agreement with the literature mentioning the difficulty in ultrasound prenatal diagnosis of the amniotic band and the frequent need of simultaneous presence of different congenital deformities to suggest the presence of ABS [16,17]. The use of most recent ultrasound technology (three- and four-dimensional ultrasonography) and the use of magnetic resonance imaging in some cases may improve the diagnosis [9,11,12]. …”
Section: Discussionsupporting
confidence: 78%
“…Fetal magnetic resonance imaging is able to visualize amniotic bands and their secondary manifestations and could be complementary to prenatal ultrasonography when ultrasound presents equivocal findings or fetal surgery is contemplated [11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings may be confirmed by fetal MRI, which is often ordered as a complimentary measure upon consideration of fetal surgery [13, 19, 20]. Amniotic bands are now being successfully released fetoscopically through minimally invasive surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be confirmed by fetal MRI, which is often ordered as a complimentary measure upon consideration of fetal surgery [13, 19, 20]. Amniotic bands are now being successfully released fetoscopically through minimally invasive surgery [19]. The intrauterine procedure is delicate and the decision to perform this surgery must be carefully weighed against the potential risks to the mother and the fetus versus continuing or terminating pregnancy [2124].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, fetal imaging is the realization of immediate ultra-high resolution imaging in all aspects [58]. The procession of US and fMRI technologies seems most promising and the most modern is the high Tesla fMRI technologies, which achieves 25-µm resolution and provides internal and external anatomy [64]. Additionally, it has been suggested that Near-Infrared Spectroscopy (NIRS) can be used in the monitoring of fetal health during the EXIT procedure considering the advantageous ability of measuring hemoglobin oxygen saturation and umbilical venous oxygenation [44].…”
Section: Future and Improvements Of Exit Proceduresmentioning
confidence: 99%